Prevention of Suicide as Perceived by Educated Adults in Ondo Metropolis, Ondo State, Nigeria - Soetan, Margaret Kehinde (Buletin Konseling Inovatif, 2025)
This study investigated prevention of suicide as perceived by educated adults in Ondo metropolis, Ondo State, Nigeria. Descriptive survey research design was adopted for this study. Population of the study consisted of all educated adults in Ondo metropolis, Ondo State. The sample comprised two hundred (200) educated adults randomly selected from the metropolis. Structured questionnaire was used as instrument to collect data for the study. Data collected was analysed using mean, ranking, t-test and analysis of variance (ANOVA). The results revealed the perception of prevention of suicide as giving people hope for a better life after current problems are resolved, developing and implementing community-based suicide prevention programmes, reducing the prevalence of conditions believed to constitute risk factors for suicide among others. The findings also revealed that gender and marital status have no significant influence on the perception of prevention of suicide (t = 2.041 and 7.142, p>0.05 respectively) while religion has a significant influence (F = 1.645, p